Labor force activities and income among young Guatemalan adults - Hoddinott, John F.; Behrman, Jere R.; Martorell, Reynaldo (SAGE Publications, 2005)
This paper considers labor force activities among adults (26 to 41 years of age in 2003) who participated as children in a nutrition supplementation trial in Guatemala. The vast majority of men are engaged in some type of income-generating activity in 2002–04. However, unlike their fathers, these men are much more likely to be engaged in wage labor, even if they remain in the original study villages. Those engaged in wage employment appear to do so steadily. Women are much more likely to be engaged in some type of income-generating activity than their mothers. For both men and women, there appears to be considerable movement in and out of own business activities. In Guatemala City, wage work is the predominant economic activity with more than half of the women interviewed working for wages; elsewhere operating non-farm businesses is the most often cited activity. For both men and women, agriculture now appears to be very much a secondary activity.